Methods of Strengthening Children's Characters through Local Wisdom Mappatulung Bugis as National Identity (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
Education serves as a means to develop intelligence, abilities, and skills to shape students' personalities. Education must be linked to reality, close to students, and relevant to society in order to have human values. The importance of strengthening character education is needed along with the weakening of the nation's character. Therefore, educational institutions in Indonesia can implement education based on local wisdom. Education-based on local wisdom is education that is based more on cultural values. Besides, character education based on local cultural wisdom also has the aim of changing the attitudes and behavior of existing human resources in order to increase work productivity to face various challenges in the future. This study aims to obtain a picture of the internalization of the value of local wisdom mappatulung as a reinforcement of character, and efforts in its preservation. This type of research is qualitative research, which is a series of studies relating to observation, data collection, and concluding. With learning based on local wisdom, it is expected to be closer to the lives of students and the community as well as to recognize the noble values of the nation's culture as reinforcing their character.